Gibberellin sources and doses on development of dwarf rice in biotests - Martins, Raphael Gonçalves; e Castro, Paulo Roberto de Camargo; Martins, Maria Bernadete Gonçalves; Silva, João Marcelo; Araujo, Diego Kitahara (Comunicata Scientiae, 2012)
Mutant of dwarf rice (Oryza sativa L.) were treated with three different concentrations of gibberellicacid originated from two sources (Gibberellin and Pro-Gibb) and submitted to the determinationof bigger height, in relation to the soil leveI. Mensurations were realized in each seven days atgreenhouse conditions under mean temperature of 25°C. lt was concluded that concentrations of 10mg L-1 of gibberellin originated from Pro-Gibb or Gibberellin was enough to promote a differentiatedperformance of the test plant. For the study of leaf anatomy Pro-Gibb presented, under all testedconcentration, increase of mesophyll thickness in relation to Gibberellin. In this analysis, source andinteraction between source and concentration applied promoted significant variations betweenthe mean data.